Comprehensive proteomic and phosphoproteomic reveal that Microcystin-LR contributed to the malignant progression of gastric cancer by estrogenic potency. (15th January 2023) - Yang, Peiyan; Zhang, Peng; Deng, Yali; Liao, Yinghao; Guo, Xinxin; Sun, Mingjun; Yin, Lihong; Liu, Ran
Abstract: The widespread cyanotoxins in drinking water pose a threat to public health induced by Microcystins (MCs). MC-LR, a predominant toxic form of MCs, has been found to play critical roles in cancer progression. The role of MC-LR in hepatocarcinogenesis has attracted extensive attention. However, as a critical digestive organ, the precise mechanism of MC-LR-induced gastric cancer is still unclear. We found that 100 nM MC-LR promoted the proliferation, migration, invasion, and anti-apoptosis of SGC-7901 cells. Quantitative proteome and phosphoproteome analysis identified differential expression patterns and aberrant pathways of SGC-7901 cells exposed to MC-LR. The results indicated that 48, 109 unique peptides from 6320 proteins and 1375 phosphoproteins with 3473 phosphorylation sites were detected after 24 h treatment of MC-LR. Proteome and phosphoproteome conjoint analysis indicated estrogen signaling pathway might play an essential step in MC-LR-treated molecular events. The mechanism underlying these changes may involve MC-LR excessively activating the estrogen signaling pathway by reducing Hsp90 phosphorylation, which results in nucleus translocation of activated ERα and Krt16 overexpression in gastric cells. In general, our results indicate multiple crucial signals triggered by MC-LR, among which MC-LR may promote the development of gastric cancer by exerting estrogenic potency. Graphical abstract: Image 1 Highlights: MC-LR promoted the development of gastric cancer by exerting estrogenic potency. The estrogen signaling pathway played a key step in MC-LR-treated molecular events. MC-LR promoted the translocation of ERα from cytosol to nucleus in SGC-7901 cells. MC-LR promoted gastric cancer progression by enhancing the expression of Krt16.